Rational Design of Heat‐Set and Specific‐Ion‐Responsive Supramolecular Hydrogels Based on the Hofmeister Effect. Issue 44 (12th September 2014) - Nebot, Vicent J.; Ojeda‐Flores, Juan J.; Smets, Johan; Fernández‐Prieto, Susana; Escuder, Beatriu; Miravet, Juan F.
Abstract Smart supramolecular hydrogels have been prepared from a bolaamphiphilic L‐valine derivative in aqueous solutions of different salts. The hydrogels respond selectively to different ions and are either reinforced or weakened. In one case, in contrast to conventional systems, the hydrogels are formed upon heating of the system. The use of the hydrogels in the controlled release of an entrapped dye is described as a proof of the potential applications of these systems. The responsive hydrogels were rationally designed by taking into account the noticeable effect of different ions from the Hofmeister series in the solubility of the hydrogelator, which was assessed by using NMR experiments. On the one hand, kosmotropic anions such as sulfate produce a remarkable solubility decrease in the gelator, which is associated with gel reinforcement, as measured by rheological experiments. On the other hand, chaotropic species such as perchlorate weaken the gel. A dramatic effect was observed in the presence of guanidinium chloride, which boosted the solubility of the gelator, in accordance with its chaotropic behaviour reported in protein science. In this case, a direct interaction of the guanidinium species with the carbonyl groups of the hydrogelator is detected by 13C NMR spectroscopy. The weakening of this interaction upon a temperature increase allows for the preparation of heat‐set hydrogelating systems.